PAS Kinase: A Nutrient and Energy Sensor “Master Key” in the Response to Fasting/Feeding Conditions - Hurtado-Carneiro, Verónica; Pérez-García, Ana; Alvarez, Elvira; Sanz, Carmen (Frontiers in Endocrinology, 2020)
The PAS kinase (PASK) protein is a nutrient and energy sensor located in the cells of multiple organs. Many of the recent findings for understanding PASK functions in mammals have been reported in studies involving PASK-deficient mice. This minireview summarises the PASK role in the control of fasting and feeding responses, focusing especially on the hypothalamus and liver. In 2013, PASK was identified in the hypothalamic areas involved in feeding behaviour, and its expression was regulated under fasting/refeeding conditions. Furthermore, it plays a role in coordinating the activation/inactivation of the hypothalamic energy sensors AMPK and mTOR/S6K1 pathways in response to fasting. On the other hand, PASK deficiency in the liver, which is responsible for physiological adaptation to fasting/feeding, prevents obesity and non-alcoholic fatty liver in mice fed with a high fat diet. This protection is explained by the re-establishment of several high fat diet metabolic alterations produced in the expression of transcription factors and key enzymes in the main metabolic pathways involved in hepatic functions to maintain metabolic homeostasis in fasting/feeding responses. This minireview covers the effects of PASK inactivation in the expression of certain transcription factors and target enzymes in several metabolic pathways under situations such as fasting, standard feeding, or high fat diets.